1990
DOI: 10.21273/hortsci.25.9.1168d
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Spot Color and Venation Inheritance and Petiole Strength Variation in Caladium

Abstract: The mode of leaf spot color, venation color and pattern inheritance and differences in the apparent strength of leaf petioles were investigated. Progeny from self pollinations of Caladium bicolor cv. Painter's Palette and two commercial cultivars (`Florida Cardinal' and `Aaron') were utilized in a pedigree and back cross breeding program to delineate and prove a proposed model for the mechanisms controlling spot and vein color inheritance as well as the inheritance of venation patterns. Differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Tremendous efforts (at least in an aroid) have been made to understand the genetic control of leaf spots and their genetic relationship with other foliar traits. Based on the segregation of leaf spots and colors at the central leaf area in the progeny of a cross between two cultivars, Zettler and Abo El-Nil (1979) proposed that one locus controlled the vein color, vein pattern, and spotting in caladium and that 'Painter's Palette', a plant collected by W. Zettler from a homesite near Campville, FL (Gager, 1991), carried alleles R and W for its red and white spots, while 'Poecile Anglais', a commercial cultivar, had the allele R# in a homozygous state for its red center on the leaf. Subsequently, Wilfret (1983Wilfret ( , 1986 showed that caladium leaf vein pattern and color were controlled by separate genetic systems.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Tremendous efforts (at least in an aroid) have been made to understand the genetic control of leaf spots and their genetic relationship with other foliar traits. Based on the segregation of leaf spots and colors at the central leaf area in the progeny of a cross between two cultivars, Zettler and Abo El-Nil (1979) proposed that one locus controlled the vein color, vein pattern, and spotting in caladium and that 'Painter's Palette', a plant collected by W. Zettler from a homesite near Campville, FL (Gager, 1991), carried alleles R and W for its red and white spots, while 'Poecile Anglais', a commercial cultivar, had the allele R# in a homozygous state for its red center on the leaf. Subsequently, Wilfret (1983Wilfret ( , 1986 showed that caladium leaf vein pattern and color were controlled by separate genetic systems.…”
mentioning
confidence: 99%
“…Subsequently, Wilfret (1983Wilfret ( , 1986 showed that caladium leaf vein pattern and color were controlled by separate genetic systems. To resolve this discrepancy, Gager (1991) performed crosses between 'Painter's Palette' and 'Aaron' or 'Florida Cardinal', sib-mated their progeny, and analyzed the segregation of leaf spots, spot color, and vein pattern. The conclusion was that a single locus controlled the expression of spotting, with two codominant alleles, S R for red spots and S W for white spots, and a recessive allele s for no spots.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough understanding of the inheritance of foliar traits is critical for improving breeding efficiency for producing desirable cultivars in these aroids (Henny, 1988). Studies to date on the inheritance of foliar traits in caladium (leaf shape, vein color, spotting, blotching, and so on) have shown that the traits are generally under simple genetic control (Deng and Harbaugh, 2006;Deng et al, 2007Gager, 1991;Wilfret, 1983Wilfret, , 1986. Diverse variation is available in a number of other leaf characteristics in caladium (Deng, personal observations).…”
Section: Resultsmentioning
confidence: 99%
“…The main breeding approach used in caladium has been hybridizations between elite cultivars or breeding lines. In recent years, significant efforts have been made to understand the mode of inheritance of several important caladium foliar traits, including leaf shape, main vein color, leaf spotting, and leaf blotching Harbaugh, 2006, 2009;Deng et al, 2008;Gager, 1991;Wilfret, 1983). It is known now that caladium leaf shape is controlled by a single locus (F) with two alleles (F and f).…”
mentioning
confidence: 99%